Technology Research of Railway Lines and Signal Equipment Three-dimensional Modeling Based on Creator - ZHANG Yan; WANG Zhi-wei (机车电传动)
For train-control equipment simulation and function verification, a set of railway lines and signal equipment three-dimensional modeling method was elaborated with virtual-reality simulation technology, and the method was realized with the software of Creator. Road module, OpenFlight format, texture and special node of Switch, and setting of LOD of Creator were introduced. The modeling method can verify function and characteristic of train-control equipment, which ensures safety of railway travel.